Influence of Service Quality and Price on Purchasing Decisions at PT Berkah Samudra Logistik Semarang - Hartiati, Anissa Sri Novira; Nurkhayati, Isnaini -; Paniya, Paniya - (Admisi dan Bisnis, 2023)
This research aims to identifying the effect of service quality and price on purchasing decisions at PT Berkah Samudra Logistik Semarang. Purposive sampling was implemented as a sampling technique for 55 respondents. The independent variables used in this study are Service Quality and Price. Meanwhile, the dependent variable used in this study is the Purchase Decision. Primary data collection using interviews and questionnaires, as well as literature studies for secondary data.”Validity test, reliability test, descriptive analysis, classic assumption test, multiple linear regression, t test, F test and coefficient of determination were chosen as the analytical method used in this study." Based on calculations that have been carried out using SPSS version 25, the results of the study shows that the result of the regression equation is Y=2.508+0.308Xâ‚+0.624Xâ‚‚+e. In addition, the results of the t test show that the results of the t test exceed the t table and produce a "significance value of less than 0.05. Likewise the results of the F test stated that the results of the F test were 20.570, while the F table was 3.18. So it can be concluded that service quality (X1) and price (X2) have a positive and strong influence on purchasing decisions (Y). The influence of the variable that has the highest influence on purchasing decisions is the price with the highest regression coefficient of 0.624